Asphyxia due to laryngeal spasm as a severe complication of awake deep brain stimulation for Parkinson's disease: a case report. Issue 1 (December 2016) - von Eckardstein, Kajetan; Sixel-Döring, Friederike; Kazmaier, Stephan; Trenkwalder, Claudia; Hoover, Jason; Rohde, Veit
Abstract Background In accordance with German neurosurgical and neurological consensus recommendations, lead placements for deep brain stimulation (DBS) in patients with Parkinson's disease (PD) are usually performed with the patient awake and in "medication off" state. This allows for optimal lead position adjustment according to the clinical response to intraoperative test stimulation. However, exacerbation of Parkinsonian symptoms after withdrawal of dopaminergic medication may endanger the patient by inducing severe "off" state motor phenomena. In particular, this can be a problem in awake craniotomies utilizing intraoperative airway management and resuscitation. Case presentation We report the case of a PD patient with progressive orofacial and neck muscle dystonia resulting in laryngeal spasm during DBS lead placement. This led to upper airway compromise and asphyxia, requiring resuscitation. Conclusions Laryngeal spasms may occur as a rare "off" state motor complication in patients with PD. Other potential causes of intraoperative difficulties breathing include bilateral vocal cord palsy, positional asphyxia, and silent aspiration. In our practice, we have adjusted our medication regimen and now allow patients to receive their standard dopaminergic medication until the morning of surgery. Neurologists and neurosurgeons performing lead placement procedures for PD should be aware of this rare but unsafe condition to most optimized treatment.